Optimization of nursing staff standards in the perioperative settings of the IRCCS University Hospital of Bologna. An improvement project - Cenacchi, Chiara; Giusti, Martina; Peghetti, Angela; Quirini, Silvio; Tinelli, Francesco; Giorgi, Sabina; Mineo, Salvatore; De Rosa, Manuela; Durante, Stefano (Frontiers in Public Health, 2025)
IntroductionThe organization of healthcare staff within operating block settings, which accommodate various surgical specialties, must consider the growing shortage of personnel and the need for resource optimization. For these reasons, we hypothesized that reorganizing the nursing staff could help reduce patient waiting lists, improve efficiency, and ensure patient safety.MethodsWe conducted a review of the existing literature on Nursing Staff Standards in the Operating Rooms in relation to surgical procedures. IRCSS University Hospital of Bologna (Italy) hospital’s operating blocks (excepted pediatric surgical rooms) were chosen as experimental contexts due to the achievement of excellence according with the research mission of this hospital. Here, all implemented surgical procedures were classified and coded using ICD-9-CM codes. For each procedure, a reclassification process was applied based on the required nursing care intensity.ResultsResults of literature review on Nursing Staff Standards in the Operating Rooms were applied, implementing a nursing roles’ reorganization. The reorganization moved from the incorporation of input from nurses and surgeons to identify areas for improvement and develop organizational solutions.DiscussionThe reorganization process allowed for a redefinition of surgical schedules and staff allocation, leading to the reallocation of nursing units that were reassigned to support the opening of a recovery room.